Current knowledge on Grapevine Trunk Diseases with complex etiology: a systemic approach - CLAVERIE, Marion; NOTARO, Martin; FONTAINE, Florence; WERY, Jacques (Phytopathologia Mediterranea, 2020)
Among all causes of grapevine decline, Grapevine Trunk Diseases (GTDs) are major concerns for grape growers. This paper reviews knowledge and proposes hypotheses on two major GTDs, esca and Botryosphaeria dieback, and assembles a conceptual model. The objective was to collect information into a sequence, from grapevine nursery propagation processes, through foliar symptom expression, to plant death in mature vineyards. Pathogen infection and colonization steps in woody vine tissues, and the hypotheses that have been formulated to explain the outburst of foliar symptoms, are reported and discussed. Factors that could aggravate or repress GTD symptoms and incidence expansion are also addressed. Vine physiology and pathology together could expand understanding of these diseases. Knowledge and hypotheses that need validation are summarized, and a conceptual model is proposed to explain the occurrence of symptoms and the influencing factors. The model could be useful to cope with the complexity of GTDs, and as a starting point for research to unravel knowledge gaps and suggest new disease management strategies.